Sir Julius Caesar's papers : reproduced in their entirety from the Lansdowne collection (volumes 123-174) in the British Library in London - Caesar, Julius, Sir, 1558-1636; Hawkins, Michael (Politics and administration of Tudor and Stuart England, 1636)
Letters and papers covering British government affairs, ranging from the 15th century to 1636, but chiefly covering the period 1583-1636.